Clinical predictive score for detecting nonalcoholic fatty liver disease with significant fibrosis in patients with metabolic syndrome. Issue 44 (5th November 2021) - Kositamongkol, Chayanis; Charernboon, Thammanard; Chaisathaphol, Thanet; Washirasaksiri, Chaiwat; Auesomwang, Chonticha; Sitasuwan, Tullaya; Charatcharoenwitthaya, Phunchai; Phisalprapa, Pochamana
Abstract : Abstract: Patients with metabolic syndrome are at a higher risk of nonalcoholic fatty liver disease (NAFLD) and liver fibrosis than the general population. Still, accessibility of screening method for NAFLD with significant fibrosis, such as transient elastography (FibroScan) are limited in some settings. This study aimed to develop a simple clinical predictive score for detecting NAFLD with significant fibrosis in patients with metabolic syndrome. A cross-sectional study was designed to obtain the data from medical records of all relevant patients who underwent transient elastography between January 2011 and December 2020 at Siriraj Hospital, Thailand. A liver stiffness cutoff value of 7.0 kilopascal was used to define the presence of significant liver fibrosis. To examine potential predictors, medical history and clinical data commonly assessed in routine practice were selected by following expert opinions and univariable statistical analysis. Backward and forward stepwise logistic regression was performed to acquire a final prediction model. To simplify the model, a weighted score was assigned for each categorized predictor. In addition, eligible cutoff values of the score and their predictive performances were determined. A total of 745 medical records were reviewed. The prevalence of NAFLD with significant fibrosis in patients with metabolic syndrome was 12.6%. Most clinical characteristics of patients with NAFLD with significant fibrosis and those non-NAFLD and NAFLD with no/mild fibrosis were quite disparate. The most practical model comprised globulin, aspartate transaminase, platelet count, and type 2 diabetes. It provided a good predictive performance with an area under the receiver operating characteristic curve of 0.828 (95% confidence interval [CI]: 0.782, 0.874). At the proper cutoff value, sensitivity and specificity were 76.6% (95% CI: 66.7%, 84.7%) and 72.4% (95% CI: 68.7%, 75.8%), respectively. The likelihood ratio of testing positive for NAFLD with significant fibrosis was 2.8 (95% CI: 2.34, 3.27) among patients with scores above the cutoff value. The first score for detecting of NAFLD with significant fibrosis in patients with metabolic syndrome was developed. This practical score, providing a good predictive performance, should be useful to help clinicians prioritize needs for further investigations among high-risk patients, especially in resource-limited settings. Abstract : Supplemental Digital Content is available in the text